Interfacial Assembly of Ultrathin, Functional MXene Films - Kim, Seon Joon; Choi, Junghoon; Maleski, Kathleen; Hantanasirisakul, Kanit; Jung, Hee-Tae; Gogotsi, Yury; Ahn, Chi Won (American Chemical Society, 2019)
MXenes are a prominent family of two-dimensional materials because of their metallic conductivity and abundant surface functionalities. Although MXenes have been extensively studied as bulk particles or free-standing films, thin and transparent films are needed for optical, optoelectronic, sensing, and other applications. In this study, we demonstrate a facile method to fabricate ultrathin (similar to 10 nm) Ti3C2Tx MXene films by an interfacial assembly technique. The self-assembling behavior of MXene flakes resulted in films with a high stacking order and strong plane- to-plane adherence, where optimal films of 10 nm thickness displayed a low sheet resistance of 310 Omega/square. By using surface tension, films were transferred onto various types of planar and curved substrates. Moreover, multiple films were consecutively transferred onto substrates from a single batch of solution, showing the efficient use of the material. When the films were utilized as gas sensing channels, a high signal-to-noise ratio, up to 320, was observed, where the gas response of films assembled from small MXene flakes was 10 times larger than that from large flakes. This work provides a facile and efficient method to allow MXenes to be further exploited for thin-film applications.
Keywords: TRANSPARENT; TRANSITION; THICKNESS; MOS2